dikriminisasi, sindrom Asperge NARASI DAN SIMBOL DISKIRIMINASI DALAM FILM “AKU JATI, AKU ASPERGER”: KAJIAN SEMIOTIKA: NARASI DAN SIMBOL DISKIRIMINASI DALAM FILM “AKU JATI, AKU ASPERGER”: KAJIAN SEMIOTIKA - Yunita; Nina Queena Hadi Putri (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
This study entitled "Visual and Narrative Elements as a Depiction of Discrimination against Asperger's: A Semiotic Study in the Film 'Aku Jati, Aku Asperger'" aims to examine and identify discrimination experienced by Asperger's people through a semiotic theory approach. The results of the study indicate that the film effectively conveys five depictions of discrimination experienced by the main character, Jati, which are caused by environmental factors, societal views, and the role of parents. Through the analysis of signs, objects, and interpretations, this study found that visual and narrative elements function as tools to increase awareness and empathy for the issues faced by Asperger's people. In addition, this study provides benefits in increasing public understanding of the challenges faced by people with disabilities, as well as encouraging constructive dialogue about social inclusion. This film can also be a source of reference for educators and parents in educating children about diversity. It is hoped that the results of this study can trigger positive changes in public attitudes towards people with disabilities and encourage the creation of a more inclusive environment, so that people with Asperger's can be accepted and appreciated in society. With increased awareness and education, we can work together to build a more equitable world for all individuals.